Effective business communication as a core element of business management - Шитель, М. О. (Мелітополь: ТДАТУ, 2019)
Business communication is a special branch of general communication. The main objective of business communication is to exchange information, wishes, attitudes etc. Through business communication, parties like owners, managers, employees, customers, investors, suppliers, bankers and general public exchange information relating to business activities
Keywords: effective communication; business communication; business management